République Démocratique du Congo (RDC/DRC) face aux difficultés de mise en œuvre de ses programmes de développement : Proposition d’un modèle participatif endogène et intégral comme voie de sortie - Kasemengo, Théodard Wahangire (IJRDO - Journal of Business Management, 2020)
Development is the purpose of any planning of public and private actors, local, regional or international community or even the scientific society to materialize its actions. In practice, issues relating to developmental programs and discourses do not reflect concrete actions either because of lack of political will or lack of sufficient means to carry out their action or more often because the various programs do not take into account the participation concerned or local resources available and the needs actually felt by the beneficiaries of its actions. The Democratic Republic of Congo (DRC) through its various programs and complementary discourses that have been contradictory for decades continues to promote local development in order to get out of underdevelopment. These different programs have not had significant effects and subsequently the country often ranked among the last in the developing countries as a result, the DRC needs another step to get out this dead end. On the theoretical models of development as a way out under development in implementation of different development programs is required. It is « the endogenous and integrated participatory approach ».This approach must be materialized through decentralization and local governance on the hand and regional integration on the other hand through the creation of pilot areas as resources of community inspiration taking into account the mobilization of locally available resources and their implementation and their good allocation to local development actions. This requires the involvement of all development actors from top to bottom right from the design stage, execution, implementation and maintenance of the development action.